Hubungan Antara Sikap Terhadap Pekerjaan Monoton Dengan Motivasi Kerja Pencatat Meter Perusahaan Daerah Air Minum (pdam) Kota Bandung - Dewi Sartika; Endah Nawangsih; Evi Mayasari (SCHEMA (Journal of Psychological Research), 2011)
PDAM is a service company. The income is mostly coming from its customer payment for their water consumption bill. Employee who has responsible to inform the water usage is the metter recording section. It is become a phenomena that the metter recording staff is never meet their target which is to record the actual consumption meter on daily basis. Iaso there are a lot of mistake during recording that will be fatal for the next process. The company is trying hard to motivated its employee by giving them an incentive, but some of them still showing un optimal result.Intention of this research is to collect emparical data regarding relationship between attitude toward monotoneus worked with workers motivation as a meter recording at PDAM Bandung.This research is using coorelational method. The subject of the research are all of 16 meter recording employee at PDAM Bandung. Using the likers scale for the questionaire. To measure the variable in the research we are using the attitude questionare to monotoneus working and motivation to work questionare.Based on the result of Spearman Correlational rank test on significancy level of 0,05 the result showing that there is high positive relationship (rs = 0,797) between attitude toward monotoneus work ed with workers motivation. Characteris monotoneus worked with workers motivationtic of monotoneus worked are: 1) No need creativity have an average possitive correlation (rs = 0,664) with attitude to work, 2) Did not have a chance for growht have a high possitive correlation (rs = 0,745), 3) Did not give a freedom of work have a high possitive correlation (rs = 0,813), 4) Do the same work and repeatedly have a high possitive correlation (rs = 0,829) with attitude to work, and 5) The work not required special skill have an average possitive correlation (rs = 0,562) with attitude to work.